The effects of gestational use of antidepressants and antipsychotics on neonatal outcomes for women with severe mental illness - Frayne, J.; Nguyen, T.; Bennett, K.; Allen, S.; Hauck, Yvonne; Liira, H. (Wiley-Blackwell Publishing Asia, 2017)
Background: Psychotropic medication use occurs in 8% of pregnancies, with rates increasing, and often multiple medications prescribed. Aims: This study aims to determine if the use of psychotropic medication, in a cohort of women with severe mental illness, increases rates of special care nursery admission and reports differences between antidepressant and antipsychotic medication use either alone or in combination. Methods: A retrospective database analysis from a cohort with severe mental illness in pregnancy identified 268 pregnant women who were grouped according to medication type. Demographic, obstetric and neonatal variables were analysed using t-tests, χ2, analysis of variance and logistic regression analysis for special care nursery admission. Results: The medication groups consisted of: women taking no psychotropic medications (n = 67); those taking antipsychotics (n = 87); those taking antidepressants (n = 55); those taking and a combination of antidepressants/antipsychotics (n = 59). Rates of special care nursery admission in women who took psychotropic medication (41.3%) were elevated compared to those who did not (26.9%) (P = 0.035), and were significantly raised when compared to the general population (P < 0.000). No significant difference occurred between the medication groups. A significant adjusted odds ratio of 2.79 (95% CI 1.286–6.049) was found for special care nursery and psychiatric admission during pregnancy but not for psychotropic medication. Conclusion: Rates of special care nursery admission are elevated in neonates of women with severe mental illness taking psychotropic medication, but were not different for monotherapy or polytherapy when prescribing antidepressants or antipsychotic medication. Additional vulnerability occurs in the neonates of women with a mental illness and paediatric presence at delivery is recommended.